Investigation of singlet oxygen efficiency of di-axially substituted silicon phthalocyanine with sono-photochemical and photochemical studies - Atmaca, Goknur Yasa (PERGAMON-ELSEVIER SCIENCE LTD, 2021)
Sono-photodynamic therapy (SPDT) is a favorable new modality for the treatment of the tumor cells. Although SPDT improves the therapeutic outcomes in cell applications, unlike PDT, SPDT studies are insufficient. In this study, to contribute to the development of SPDT, a promising sensitizer was synthesized, characterized, and analyzed photophysico-chemical properties. Afterwards, the singlet oxygen quantum yield of the sensitizer was calculated by both photochemical and sono-photochemical studies. When the methods are compared, the sono-photochemical studies (Phi(Delta) = 0.71 in DMSO, 0.65 in DMF) were found more effective than the photochemical studies (Phi(Delta) = 0.47 DMSO, 0.41 in DMF) in terms of producing singlet oxygen. This report will pave the way for the synthesis of new sensitizers to be used in SPDT. (C) 2020 Elsevier Ltd. All rights reserved.
Keywords: Sonochemical properties; Photochemical properties; Phthalocyanine; Singlet oxygen; Chemistry; Crystallography